Family planning and sustainable development in Bangladesh : empowering marginalized communities in Asian contexts - Islam, M. Rezaul (Diverse perspectives on creating a fairer society, 2024)
Exploring tailored family planning strategies for marginalized groups, Family Planning and Sustainable Development in Bangladesh delves into comparative insights from Asian contexts, providing actionable approaches to empower and transform communities, foster sustainable development and improve reproductive health outcomes. Featuring comprehensive case studies and analysis from diverse Asian regions and religious communities, M. Rezaul Islam provides readers with a nuanced understanding of family planning strategies tailored to unique cultural contexts. Seamlessly connecting family planning with the Sustainable Development Goals (SDGs), Islam demonstrates its potential for uplifting the most vulnerable communities in Bangladesh and beyond. Dissecting global population trends and cultural influences on family planning, chapters navigate knowledge, attitudes, practices, and communication strategies, unveiling avenues for transformation and sustainable change within Asian communities. Concluding by presenting actionable policy implications that stakeholders can adopt to drive positive change at both community and systemic levels, Family Planning and Sustainable Development in Bangladesh is a powerful addition to the contemporary landscape of global health, development, and social progress.